1996
DOI: 10.1017/s1323358000020713
|View full text |Cite
|
Sign up to set email alerts
|

Axel: A Balloon-borne X-ray Astronomy Experiment

Abstract: Following a successful program to investigate the physics of ultra-high-pressure proportional counters, a counter array has been developed for hard X-ray astronomy. A parallel investigation has evaluated the performance of a large-area phoswich scintillator detector for the same purpose. The two detectors have been integrated in a balloon-borne payload, the Astrophysical X-ray Experimental Laboratory (AXEL). This paper describes the instrumentation aboard the payload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The RMC was first proposed for X-ray astronomy by Schnopper et al (1968). The RMC technique was successfully used in a number of rocket flights (Schnopper et al 1970;Cruise & Willmore 1975) and balloon-borne experiments (Staubert et al 1983;Ubertini et al 1985;Sood et al 1996) for hard X-ray imaging. Nishimura et al (1978) used a balloon-borne wide-field RMC instrument to localise gamma-ray bursts.…”
Section: Introductionmentioning
confidence: 99%
“…The RMC was first proposed for X-ray astronomy by Schnopper et al (1968). The RMC technique was successfully used in a number of rocket flights (Schnopper et al 1970;Cruise & Willmore 1975) and balloon-borne experiments (Staubert et al 1983;Ubertini et al 1985;Sood et al 1996) for hard X-ray imaging. Nishimura et al (1978) used a balloon-borne wide-field RMC instrument to localise gamma-ray bursts.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the efforts of the leading groups were devoted to the design of new imaging experiments, especially for long duration balloon flights, e.g. EXITE2 (Grindlay 1998), ALISE , AXEL (Sood et al 1996), MARGIE (Cherry et al 1995), LASE (D 'Silva et al 1998). An interesting review on the significant scientific results obtained with balloon experiments was reported by Teegarden (1994).…”
Section: Satellite Missions and Balloon Experiments In The 1990smentioning
confidence: 99%